FAKTOR-FAKTOR KEPATUHAN PERAWAT YANG BERHUBUNGAN DENGAN PELAKSANAAN PENGKAJIAN SPIRITUAL PASIEN DI RUMAH SAKIT âXâ BANDUNG - Nurmaida S, Sofia Gurnia (Indonesian Journal of Nursing Health Science, 2016)
AbstractPain is a form of life or circumstances beyond normal limits and thus requires medical attention and care in health care facilities. Nurses as a profession of the healthcare team responsible for helping clients safely and comfortably. One of the nurseâs roles in health care is spiritual fulfillment. Spiritual assessment is part of a holistic nursing assessment. Spiritual fulfillment clients can reduce pain and aid in healing physical and mental. The purpose of the study determines the relationship between the factors of compliance with the implementation of a spiritual assessment of patients at Hospital